2002
DOI: 10.1079/pns2002150
|View full text |Cite
|
Sign up to set email alerts
|

Fortification strategies to meet micronutrient needs: sucesses and failures

Abstract: Food fortification is likely to have played an important role in the current nutritional health and well-being of populations in industrialized countries. Starting in the early part of the 20th century, fortification was used to target specific health conditions: goitre with iodized salt; rickets with vitamin D-fortified milk; beriberi, pellagra and anaemia with B-vitamins and Fe-enriched cereals; more recently, in the USA, risk of pregnancy affected by neural-tube defects with folic acid-fortified cereals. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 19 publications
2
84
0
1
Order By: Relevance
“…And finally, campaigns can be used to target members of the affected population-and/or the people who influence them-to encourage them to seek and purchase only fortified food staples. A recent review of the literature concluded that the most effective micronutrient fortification programs are those that take measures both to ensure the wide availability of fortified foods and to create consumer demand for such foods (13).…”
Section: Discussionmentioning
confidence: 99%
“…And finally, campaigns can be used to target members of the affected population-and/or the people who influence them-to encourage them to seek and purchase only fortified food staples. A recent review of the literature concluded that the most effective micronutrient fortification programs are those that take measures both to ensure the wide availability of fortified foods and to create consumer demand for such foods (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although the food fortification is positively evaluated in many countries, this assertive is not clear for the iron fortification (16) . Besides, the real effects of this policy are not yet clear and must be considered, once declines in the anemia prevalence can result in structural changes in life conditions and, therefore, in the food offer, in eating patterns and in the improvement of access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous foods have long been fortified in economies in which food production and marketing systems are highly industrialized, integrated, and readily reach the consumer [330,331]. Fortification is likely to be most effective when one or more food vehicles are widely consumed by high-risk groups, and their intake is reasonably narrow across other segments of a population (to minimize risk of overconsumption), processing and distribution are centralized (in a limited number of facilities to maintain quality control), organoleptic change from addition of vitamin A is imperceptible over time under ambient conditions, and costs of fortification are both small relative to the product itself and absorbable by the consumer [2,329,330,332,333].…”
Section: Fortifi Cationmentioning
confidence: 99%